Pengaruh Teknik Amplifikasi Dalam Matan Jazariyyah Terhadap Kualitas Terjemahan Dan Penerapan Tajwid Dalam Membaca Al-Quran - Farhan Muhammad Ismail; Muhammad Yunus Anis (An Nazhair: Journal of Arabic Education, 2025)
This study aims to examine the translation technique of amplification in translating the text of Matan Jazariyyah, a classic work in the field of tajweed, as well as its impact on the quality of the translation and the application of the Qur'anic reading law, namely the science of tajweed. The amplification technique is used by adding information in the translation to explain technical terms such as ghunnah, ikhfa', mad thabi'i, istifāl, and tarqiq, which are generally difficult to understand by lay readers. The method used is descriptive qualitative with a content analysis approach. This study found that amplification improves the readability and acceptability of translated texts, facilitates the understanding of tajweed concepts, and supports practical tajweed learning. The four main forms of amplification found in the data, namely explicitation, paraphrasing, additions, and annotations, each contribute to the clarity of meaning and conveyance of context. However, if applied excessively or inaccurately, these techniques have the potential to degrade the accuracy of the original meaning and lead to misunderstandings. Therefore, the application of amplification techniques should consider the balance between accuracy and readability, and be based on a good command of tajweed. This study provides an important contribution to the development of translation strategies for religious texts, especially in Qur'anic and tajweed education among non-Arabs.